1988
DOI: 10.3354/meps049141
|View full text |Cite
|
Sign up to set email alerts
|

Standing stock and production of phytoplankton in the estuary of the Chang-jiang (Yangste River) and the adjacent East China Sea

Abstract: We determined cell density and dominant species of eukaryotic phytoplankton, chlorophyll concentration and primary production in the Changjiang estuary and dilution zone in January and July 1986. In winter, phytoplankton was dominated by small cells (< 10 pm), closely associated to particulate matter. In summer, the most striking feature of chlorophyll and primary production distributions was the presence of sharp maxima localized about 100 km offshore at salinities between 25 and 30 960 and related to diatom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 25 publications
4
36
3
Order By: Relevance
“…The high density area of phytoplankton would move toward the river's mouth with very high concentration of nutrients, and possibly arouse abnormal proliferation of phytoplankton (Shen et al 1992). Zhang et al(1999) thought that the Three Gorges Dam may reduce considerably the sediment load to the estuary, which in turn affects the region where photosynthesis is in radiation limitation and facilitates the primary production sustained by riverine nutrient supply (Ning et al 1988). Chen (2000) suggested that whether the East China Sea will become eutrophicated, actually depends on the amount of phosphorus supply supported by on-shore advection.…”
Section: Historical Changes In Nutrient Concentrations In the Changjimentioning
confidence: 99%
“…The high density area of phytoplankton would move toward the river's mouth with very high concentration of nutrients, and possibly arouse abnormal proliferation of phytoplankton (Shen et al 1992). Zhang et al(1999) thought that the Three Gorges Dam may reduce considerably the sediment load to the estuary, which in turn affects the region where photosynthesis is in radiation limitation and facilitates the primary production sustained by riverine nutrient supply (Ning et al 1988). Chen (2000) suggested that whether the East China Sea will become eutrophicated, actually depends on the amount of phosphorus supply supported by on-shore advection.…”
Section: Historical Changes In Nutrient Concentrations In the Changjimentioning
confidence: 99%
“…NPP rates in the Zaire plume were at least an order of magnitude lower, ranging from 0.05 to 0.25 g C m 22 d 21 (Cadée 1978). The much higher NCP rates observed in the Mississippi River plume may be attributable to the higher nutrient (DIN) concentrations in the plume (0-32 mmol kg 21 at salinities 20-30) than in the cases for the Amazon and Zaire plumes (0-12 and 0-8 mmol kg 21 , respectively; Van Bennekom et al 1978;DeMaster and Pope 1996;Lohrenz et al 1999), and lower turbidity than that of the Changjiang and Zaire River plumes (Eisma et al 1978;Ning et al 1988;Trefry et al 1994).…”
Section: Processes Influencing Ph Dic and Talk Distributions-mentioning
confidence: 98%
“…For example, NCP rates of 0.9-1.6 g C m 22 d 21 were reported for the Amazon plume (Ternon et al 2000), and NPP rates of 1.5 g C m 22 d 21 were observed in the Changjiang plume in a warm season (Ning et al 1988). NPP rates in the Zaire plume were at least an order of magnitude lower, ranging from 0.05 to 0.25 g C m 22 d 21 (Cadée 1978).…”
Section: Processes Influencing Ph Dic and Talk Distributions-mentioning
confidence: 99%
“…This kind of distribution is specific to upwelling areas or, at least, indicates intense vertical convection carrying nutrients released from sediments up to the surface, providing a basis for primary production. Ning et al (1988) and Tian (1989) have reported high primary production in this area. Additionally, activities of nekton and zooplankton, which produce NH: (Gu 1982;Shi 1986) can contribute to the formation of this high NH: region.…”
Section: Nutrients In Summermentioning
confidence: 99%
“…Ning et al (1988) and Tian (1989) reported a highest primary production region just outside the plume water fronts in the Changjiang Estuary. According to the turbidity measurements performed during the cruise, the content of suspended matter was below 10 mg/l outside the plume water fronts in surface waters whereas it was above 100 mg/l inside, with some values higher than 500 mg/l at the turbidity maximum.…”
Section: Nutrients In Summermentioning
confidence: 99%